A mitigation of channel crosstalk effect in dispersion shifted fiber based on durability of modulation technique - Ali Shaban; Murad Obaid Abed; Ehab Abdul Razzaq Hussein; H. J. Abd (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In fiber optics the Four Wave Mixing (FWM) has the harmful effect of an optical transmission system that can severely limit Wavelength Division Multiplexing (WDM) and reduce the transmission aptness. This work preset the durability of the different modulation format was tested to FWM by using Dispersion Shifted Fiber (DSF). Moreover, the performance of the proposed system is surveyed by changing the fiber length and applying an information rate of 200 Gb/s. The experimental results show that the FWM capacity has decreased significantly by more than 14 dB when applying Return to Zero (RZ) modulation form. In addition, in terms of the propsed system performance in the first channel and with 700 km distance, it was observed that the lower Bit Error Rate (BER) in the normal RZ modulation is equal to 1.3×10-13. As well as it is noticeable when applied the Non Return to Zero (NRZ), the Modified Duobinary Return to Zero (MDRZ) and Gaussian modulation, the system performance will be quickly changed and getting worse, where the BERs increased to 1.3×10-4, 1.3×10-6 and 1.3×10-2 consecutively at same channel and for the same parameters.